2021
DOI: 10.1007/s11356-021-15608-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of aerosol optical properties at two urban areas in the north of Vietnam with the implication for biomass burning impacts

Abstract: The spatiotemporal distribution and characterization of aerosol optical properties in the north of Vietnam were investigated extensively using the long-term measurements obtained from Moderate Resolution Imaging Spectroradiometer (MODIS) (from 2010 to 2019) and two Aerosol Robotic Network (AERONET) stations (Nghia Do, Hanoi City, from 2010 to 2019 and Son La from 2012 to 2019) located in fast-developing urban areas. This study also analyzed the tendency of AOD over different wavelengths as well as the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
3
0
1
Order By: Relevance
“…Low temperatures can lead to the formation of secondary aerosols during the winter months (Duan et al, 2020;Mues et al, 2018). Previous studies have shown the importance of secondary organic aerosols (SOA) in contributing to PM2.5 (Bui et al, 2022;Mancilla et al, 2015). autumn.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Low temperatures can lead to the formation of secondary aerosols during the winter months (Duan et al, 2020;Mues et al, 2018). Previous studies have shown the importance of secondary organic aerosols (SOA) in contributing to PM2.5 (Bui et al, 2022;Mancilla et al, 2015). autumn.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Biomass burning has been reported as one of the important regional and/or local sources of poor air quality in Southeast Asian countries [10,31,[60][61][62][63][64][65][66][67][68]. As an effort to further identify the source regions of fires associated with the seasonal air masses which influence the seasonal variation of atmospheric PM 2.5 , the integrated maps of MODIS cumulative FRP and air mass trajectories at the measurement site for the summer period (July 2020) and winter period (January 2021) are displayed in Figure 7.…”
Section: Influences Of Seasonal Meteorological Conditions and Regiona...mentioning
confidence: 99%
“…Tính đến cuối năm 2019, trên địa bàn Hà Nội có khoảng 6,0 triệu xe máy và 787.000 ô tô [5]. Khí thải từ các phương tiện giao thông được coi là một trong những nguồn gây ô nhiễm không khí chính ở Hà Nội [9], bên cạnh một số nguồn khác như đốt nhiên liệu cho sinh hoạt và công nghiệp, đốt chất thải, xây dựng và nguồn lan truyền từ xa [10,11].…”
Section: Khu Vực Nghiên Cứu Và Vị Trí Lấy Mẫuunclassified